INFLUENCE OF PLANT DENSITIES AND PLANTING DATES ON THE POPULATION OF PIGEONPEA FLOWER BLISTER BEETLES IN OWERRI, IMO STATE, NIGERIA - S. A. DIALOKE,; F. O. OJIAKO,; B. O. BOSAH,; C. A. PETER-ONOH, (The Bioscan, 2013)
The early maturing pigeonpea cultivar (ICPL 84023) was evaluated to ascertain the extent of protection to which plant densities and dates of planting will have on the population of blister beetles (Mylabris pustulata Thunberg (Coleoptera: Meloidae). Field trial was carried out at the Postgraduate Teaching and Research Farm, Department of Crop Science and Technology, Federal University of Technology, Owerri Imo State in April, July and October 2009 and repeated in 2010. Experiment was laid out in a 3 x 4 factorial and treatments consisted of four plant populations namely: 190,474 plants ha-1, 125,000 plants ha-1, and 80,000 plants ha-1, 55,556 plants ha-1 with three planting dates, April, July, and October. The result showed high population of M. pustulata on higher plant densities than at lower plant densities. Also April planting season recorded very high population of the M. pustulata on the pigeonpea while there was absence of the blister beetles during July and October planting seasons. Appropriate plant density and time of sowing may be an important integrated management of M. pustulata population in this locality.